2012
DOI: 10.1242/jcs.112722
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 promotes focal adhesion disassembly and cell motility through phosphorylation of FAK in growth factor-stimulated cells

Abstract: SummaryThe crosstalk between spatial adhesion signals and temporal soluble signals is key in regulating cellular responses such as cell migration. Here we show that soluble growth factors enhance integrin signaling through Akt phosphorylation of FAK at Ser695 and Thr700. PDGF treatment or overexpression of active Akt1 in fibroblasts increased autophosphorylation of FAK at Tyr397, an essential event for integrin turnover and cell migration. Phosphorylation-defective mutants of FAK (S695A and T700A) underwent au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…phosphorylation of FAK at Tyr 397 (Higuchi et al, 2013). However, we find no evidence that LAR regulates FAK activity and phosphorylation of CDK1 Thr 161 in LARΔP cells is not affected by PDGF (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…phosphorylation of FAK at Tyr 397 (Higuchi et al, 2013). However, we find no evidence that LAR regulates FAK activity and phosphorylation of CDK1 Thr 161 in LARΔP cells is not affected by PDGF (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…This contrasts with the classical view of this pathway in which FAK is an upstream component of the pathway and largely insensitive to PI3K (7,8,10). However, recent reports have independently shown that serine/threonine phosphorylation of FAK by Akt, a major effector of PI3K, enhances its activation (53,54). Our results provide a plausible explanation for this apparent discrepancy in the literature because we showed that FAK becomes sensitized to PI3K-Akt regulation only when GIV enhances this pathway above a critical threshold.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, we found that treatment with pan-EGFR inhibitors also resulted in down regulation of cell cycle key regulators such as Cyclin D1 and Cyclin A, implicating that down regulation of ERK1/2 and AKT pathways affects cell cycle progression. Moreover, a recent study has exemplified the novel function of AKT which promotes FAK auto-phosphorylation for cell migration and motility [49]. Together these results indicate that canertinib affects both the proliferative (ERK) and survival (AKT) pathways.…”
Section: Discussionmentioning
confidence: 89%